Creative process of elementary school teacher education students in making Ecoprint: aesthetic habitus studies : English - Probosiwi; Setyaningrum, Fery (Taman Cendekia: Jurnal Pendidikan Ke-SD-an, 2022)
The purpose of writing this article is to describe the creative process of making an ecoprint by students. The background of the writing is that there is a relationship between students' creative process in making patterns with aesthetic habitus in the eco print stages. The method used is qualitative with a narrative approach. The subjects studied were even semester students for the 2021/2022 academic year, while the object of study was making an ecoprint in groups. Data collection techniques were carried out using observation and document review. The data analysis selected is narrative techniques. The study results show that steamed ecoprint works are carried out through a creative process involving habitus to achieve the work's aesthetics. The achievement of aesthetic habitus in the creative process is supported by five stages, namely: (1) the stage of understanding or problem formulation; (2) the preparation stage; (3) the incubation stage; the (4) stage of illumination; (5) verification stage. The essence of habitus is the condition of any objectification and perception described in the actions taken by PGSD UAD students who apply to learn behavior with nature and identify natural materials in ecoprint techniques and with assistance from supporting lecturers and art practitioners. Keywords: Creative process, Ecoprint, Aesthetic habitus